In silico target identification and pharmacokinetic profiling of 2-aryl-quinoline-4-carboxylic acid derivatives as potential antileishmanial agents - da Silva, Marília Cecília; Viana, Jéssika de Oliveira; Olegário, Tayná Rodrigues; Sabino, Jayne Maria; Barbosa, Euzébio Guimarães; Chaves, Elton José Ferreira; Rocha, Gerd Bruno; Lima-Junior, Claudio Gabriel; Weber, Karen Cacilda (Frontiers in Pharmacology, 2025)
IntroductionLeishmaniasis remains a major neglected tropical disease, and new therapeutic strategies are urgently needed. This study aimed to identify the molecular target of 2-aryl-quinoline-4-carboxylic acid derivatives and assess their pharmacokinetic profiles.MethodsAn integrated in silico workflow was employed, including inverse virtual screening (IVS), molecular docking, molecular dynamics (MD) simulations, and ligand-based similarity searches in public chemical databases. Pharmacokinetic and toxicity predictions were also performed.ResultsIVS highlighted Leishmania major N-myristoyltransferase (LmNMT) as the most frequent high-affinity target. Docking and MD simulations demonstrated stable binding of selected compounds, with compound 2d showing the highest docking scores and compound 1g displaying enhanced affinity after conformational relaxation of the enzyme. Ligand-based similarity search confirmed the superior predicted binding affinity of the studied compounds compared to known molecules. Most derivatives exhibited favorable predicted pharmacokinetic properties and comparable or improved profiles relative to DDD85646.DiscussionThese results support the potential of the 2-aryl-quinoline-4-carboxylic acid scaffold as a basis for the development of novel LmNMT inhibitors with promising pharmacokinetic properties, paving the way for further experimental validation.